ANALISA KEBUTUHAN AIR BERSIH UNTUK OPERASIONAL HARIAN DAN SISTEM PEMADAM KEBAKARAN SPRINKLER GEDUNG UTAMA BARU RUMAH SAKIT BHAYANGKARA PALEMBANG - R.A. Sri Martini; Erny Agusri; M. Nur Ridho Hasan (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
The Bhayangkara Hospital Palembang has the main building with four floors and about 6102.52 m2 building area and 7538m2 surface area. It has 173 beds, 45 toilets, and 369 employees. In the new building, there are 3 water sources, which are the tank fiberglass panels with the capacity of 403 m3 and 90 m3, and a roof tank with the capacity of 16 m3. With the additional building, the water needs are also increased in order to fulfil the daily operational water needs and the new main building’s sprinkler fire extinguisher system. The purpose of this study is to know the amount of water that must be provided for the daily operational. Analysis methods and data processing in this study are descriptive analysis methods, which the existing data are separated from the data with a form of numbers, either there are primary or secondary data. The data analysis includes: the maximum clean water needs for the daily operational based on the amount of patient’s bed (500 liter/bed/day), the hospital’s employees (120 liter/person/day), toilets (39 liter/day), sinks (30 liter/day), urinals (30 liter/day), showers (75 liter/day), and janitors (0.5 liter/m2/day), and the water needs from the sprinkler fire extinguisher system. Based on the calculations, the maximum clean water needs for daily operation is 132749 m3/day and the water needs for the sprinkler fire extinguisher is 992.358 m3 for 30 minutes, while the available amount of clean water is 146 m3/day. It can be concluded that the Bhayangkara Hospital’s water sources can only fulfilled the hospital’s daily operational water needs. Then, there will be plans to make the bigger volume of the ground water tank for 1.120 m3.